PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION TERHADAP KETERAMPILAN MENULIS BERITA - Eliza, Lusy Putri; Arief, Ermawati; Ratna, Ellya (Universitas Negeri Padang, 2016)
ABSTRACTÂ This research aims to (1) describe grade ability in writing news before and after using model cooperative learning type group investigation (2) describe the effect of the use of model cooperative learning type group investigation, toward ability in writing news. The type of this research is quantitative research done using experimental design. There are three results of the research are (1) ability in writing news before using model cooperative learning type group investigation with average 65,34, (2) ability in writing news Â before using model cooperative learning type group investigation with average 78,57. (3) based on t-test, using model cooperative learning type group investigation toward ability in writing news because ttable<tcount (1,72<4,26)Â Kata Kunci: pengaruh, model, group investigation, berita